2002
DOI: 10.1111/j.1572-0241.2002.05627.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic pancreas presenting as dysphagia

Abstract: Heterotopic pancreatic tissue, also known as a pancreatic rest, is an uncommon congenital anomaly defined as extrapancreatic tissue located far from the pancreas and without connection via vascular or anatomical means to it. Such tissue may occur throughout the GI tract but has a propensity to affect the stomach and the proximal small intestine. The majority of patients with pancreatic heterotopia are asymptomatic, but when symptoms occur, they can present in a variety of ways. We report a case of a patient wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 18 publications
0
21
0
6
Order By: Relevance
“…On EUS, HP often appears as a solid submucosal mass of low echogenicity compared to the hyperechoic submucosa, and it is isoechoic to the hypoechoic muscularis propria layer (14). In our patient group, however, only 63,6% (38/60) were hypoechoic.…”
Section: Endoscopic Resection For Gastric Hpsmentioning
confidence: 44%
“…On EUS, HP often appears as a solid submucosal mass of low echogenicity compared to the hyperechoic submucosa, and it is isoechoic to the hypoechoic muscularis propria layer (14). In our patient group, however, only 63,6% (38/60) were hypoechoic.…”
Section: Endoscopic Resection For Gastric Hpsmentioning
confidence: 44%
“…Nevertheless, Shalaby et al [18] reported a case of esophageal HP diagnosed with biopsies obtained with a jumbo forceps. Teixeira [19] has described the use of ethanol injection to create an artificial ulcer that then facilitated the removal of sufficient submucosal tissue to establish the diagnosis of HP.…”
Section: Discussionmentioning
confidence: 99%
“…According to Shalaby et al a second biopsy using jumbo forceps allowed for retrieval of a representative specimen [5]. Pre-interventional biopsy showed ectopic pancreas in only one of the five biopsied patients (case 1).…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic pancreas is most commonly found in the upper GI-Tract (in 90% of all cases in the stomach, duodenum or upper jejunum) [3]. The highest incidence of ectopic pancreas occurs in the 4 th , 5 th and 6 th decade, 2-3 times more frequently in males [4,5]. The condition is usually asymptomatic and may become clinically evident when complicated by pancreatitis [6], malignancy [7,8], obstruction [9], ulceration and bleeding [10,11].…”
Section: Introductionmentioning
confidence: 99%